2017
DOI: 10.1097/md.0000000000009195
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the corticofugal tract from the secondary motor area in a Parkinson's disease patient with limb-kinetic apraxia

Abstract: Rationale:In this case report, we describe a Parkinson's disease (PD) patient with limb-kinetic apraxia (LKA) in whom degeneration of the corticofugal tract (CFT) from the supplementary motor area (SMA) was observed in diffusion tensor tractography (DTT).Patient concerns:A 63-year-old woman presented with a loss of dexterity in both upper extremities, which indicated LKA, and typical PD-related symptoms, including a gait disturbance with a short step, resting tremor in both upper extremities, and rigidity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…21,22 It also allows for three-dimensional reconstruction of the CFTs from the secondary motor area. 10,11,18,23 Some previous studies demonstrated the injury of CFTs from the secondary motor area in patients with traumatic brain injury, corona radiata infarct, and Parkinson's disease. 18,23,24 However, there is currently a lack of evidence regarding limb kinetic apraxia caused by injury of the CFTs from the secondary motor area in patients with MCA territory infarction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 It also allows for three-dimensional reconstruction of the CFTs from the secondary motor area. 10,11,18,23 Some previous studies demonstrated the injury of CFTs from the secondary motor area in patients with traumatic brain injury, corona radiata infarct, and Parkinson's disease. 18,23,24 However, there is currently a lack of evidence regarding limb kinetic apraxia caused by injury of the CFTs from the secondary motor area in patients with MCA territory infarction.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In the human brain, motor function is associated with various neural tracts, including the corticofugal tract (CFT), corticospinal tract (CST), corticoreticulospinal tract, and corticorubrospinal tract. [10][11][12][13][14][15] The primary function of CFTs from the secondary motor area, which is classified as the premotor cortex (PMC) and supplementary motor area (SMA), is motor planning. 16 Consequently, injury of the CFTs from the secondary motor area commonly induces limb kinetic apraxia, which is the inability to make precise or exact movements with the hands and upper or lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…Several neural tracts related to motor function, including the CST, CFT, and corticoreticulospinal tract, could be reconstructed using a DTT reconstruction method [ 15 , 18 , 28 30 ]. As a result, many DTT-based studies have reported that LKA is related to injuries of the above neural tracts in various brain pathologies [ 2 , 7 , 15 19 , 23 , 32 34 ].…”
Section: Introductionmentioning
confidence: 99%